Bashkir names of persons in Russian written sources of the 16th–18th centuries - Khisamitdinova, Firdaus G.; Mukhtarov, Timur G. (The New Research of Tuva, 2023)
This article discusses Bashkir names of persons recorded in Russian-language sources of the 16th–18th centuries. The main sources for writing the article were separate volumes of “Materials on the History of the Bashkir ASSR (Bashkortostan)” and “Documents and Materials on the History of the Bashkir People (1574–1798)”. These sources mainly contain materials on the socio-economic, socio-political history of Bashkiria and the Bashkirs of the 16th–18th centuries. This information is a valuable source on the history of the Bashkir language. These documents contain information on both the appellative and onomastic vocabulary of that time. Some names of persons reflected in these sources are now completely out of use, the others have passed into the category of historical and passive vocabulary of the Bashkir language. Therefore, the only way to study this kind of vocabulary is to research on written monuments. In total, more than 200 documents were used. More than 300 lexemes have been extracted from these written sources. Of these, about 100 naming units are names of Bashkir persons, which the authors break up into five groups. Among them, a fairly large group consists of the names of people associated with the class and property characteristics of a person. The article analyzes a part of the Turkic-Bashkir and borrowed names from this group. The authors have found that most of the names are mainly of common Turkic origin and some are of common Altai origin. Borrowed names are mainly associated with Arabic and Persian. Names borrowed from the Russian language are also observed.